Epistemologi Tafsir dalam Jami’ al-Bayan: Analisis Pemikiran Ibn Jarir at-Tabari - Lufaefi, Lufaefi (STAINI Press, 2024)
Jami 'al-Bayan is a fanciful commentary among the scholars of the Qur'an. This commentary was composed by early-century commentators on the map of Qur'anic interpretation. Although this commentary has been widely studied, there are still many unknowns in it, especially with regard to this type of interpretation and the method used in its writing. This paper will explore the discussion of Jami 'al-Bayan's commentary, especially highlighting what exactly is the pattern and method. In this paper it is found that the style used in the Tabari is riwa'i, this can be proven when he interprets every verse never separated from the history of the prophet, even with its diversity. The method used in the commentary is al-Quran bi al-Quran and bi ar-riwayah.